Stability and universal encapsulation of epitaxial Xenes. (9th December 2020) - Molle, Alessandro; Faraone, Gabriele; Lamperti, Alessio; Chiappe, Daniele; Cinquanta, Eugenio; Martella, Christian; Bonera, Emiliano; Scalise, Emilio; Grazianetti, Carlo
Abstract : We propose a sequential Al2 O3 encapsulation of silicene as a solution to degradation, that can be extended to the general case of epitaxial Xenes on substrates. Abstract : In the realm of two-dimensional material frameworks, single-element graphene-like lattices, known as Xenes, pose several issues concerning their environmental stability, with implications for their use in technology transfer to a device layout. In this Discussion, we scrutinize the chemical reactivity of epitaxial silicene, taken as a case in point, in oxygen-rich environments. The oxidation of silicene is detailed by means of a photoemission spectroscopy study upon carefully dosing molecular oxygen under vacuum and subsequent exposure to ambient conditions, showing different chemical reactivity. We therefore propose a sequential Al2 O3 encapsulation of silicene as a solution to face degradation, proving its effectiveness by virtue of the interaction between silicene and a silver substrate. Based on this method, we generalize our encapsulation scheme to a large number of metal-supported Xenes by taking into account the case of epitaxial phosphorene-on-gold.